Pendidikan Karakter dalam Tembang Macapat Mijil - Ikawati, Iis Ikawati; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The purpose of this study is to interpret the array of macapat songs, especially Mijil songs as a support for character education. The type of research used is library research. To sharpen the analysis of descriptive qualitative methods, content analysis techniques are used, namely scientific analysis based on the content of messages in communication. Message content in communication. The results of this study are in the form of character education values that exist in the mijil song, these values include being smart, humble, yielding, not arguing, simplicity, and not gossiping. The community and education actors can explore cultural values or local wisdom to provide a stimulus in learning with different, interesting, and fun nuances.